Roles of NR1I3 and NR1H4 polymorphisms in the susceptibility to antituberculosis drug-induced liver injury in China: a case‒control study - Xu, Xiaoyan; Chen, Ruina; Lu, Lihuan; Cheng, Jingru; He, Xiaomin; Pan, Hongqiu; Zhang, Meiling; Yi, Honggang; Tang, Shaowen (Frontiers in Genetics, 2024)
Objective: The pathogenesis of antituberculosis drug-induced liver injury (AT-DILI) remains largely unknown. The current investigation aimed to determine the genetic contribution of the nuclear receptor subfamily 1 Group I member 3 (NR1I3) and nuclear receptor subfamily 1 Group H member 4 (NR1H4) genes to the risk of AT-DILI in the Chinese population.Methods: A 1:4 matched case-control study was conducted, and five single nucleotide polymorphisms (SNPs) in the NR1I3 and NR1H4 genes were detected and assessed. Utilizing a multivariate conditional logistic regression model, the effects of haplotype and genotype on the risk of AT-DILI were examined. Extended subgroup analysis was carried out based on patient sex and hospital. The distribution of the peak value of serum liver enzymes also compared among different genotypes.Results: 224 AT-DILI cases and 896 controls were included in this study. No significant difference was observed in genotypes or haplotypes frequencies between AT-DILI cases and controls. However, comparisons of liver function indicators revealed significant differences in the peak values of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and total bilirubin (TBil) among patients with different genotypes of NR1H4 rs56163822 (GG vs. GT vs. TT, 27.1 U/L vs. 26.0 U/L vs. 23.0 U/L, p = 0.020; 34.0 U/L vs. 31.0 U/L vs. 30.6 U/L, p = 0.008; 15.5 μmol/L vs. 15.0 μmol/L vs. 13.7 μmol/L, p = 0.029, respectively), as well as in the peak values of ALT and AST among male patients with different genotypes of NR1H4 rs56163822 (29.0 U/L vs. 26.9 U/L vs. 22.6 U/L, p = 0.002; 34.0 U/L vs. 32.0 U/L vs. 30.5 U/L, p = 0.019, respectively).Conclusion: Based on this 1:4 individual-matched case-control study, the SNP rs56163822 in the NR1H4 gene may be linked to the susceptibility to AT-DILI in Chinese patients receiving anti-TB treatment. Further studies in larger varied populations are needed to validate our findings.